(untitled) (Revista Archai, 2023)
In the Lysis, Socrates claims to be looking for an account of what kind of quality in another person or object stimulates friendship or love (philia). He goes through a series of proposals, refuting each in turn. In the end, he throws us back to the point from where the arguments started, declaring an aporetic outcome. What is the purpose of this apparently futile and circular inquiry? Most interpreters try to reconstruct a theory of friendship or love from the arguments of this dialogue. Against such a doctrinal reading, this essay defends an “aporetic reading” of the dialogue and connects it to its protreptic function. Starting with a preliminary discussion of what defines an aporetic dialogue and what distinguishes indirect protreptic from explicit protreptic discourse, the essay then analyzes the aporetic method of the Lysis, distinguishing it from aporetic discourse in some of his earlier dialogues. Finally, it analyzes how, and for what kind of audience, the Lysisfunctions as an indirect protreptic. This includes a comparison with the protreptic use of aporetic argumentation in the Euthydemus.